FAIM Is a Non-redundant Defender of Cellular Viability in the Face of Heat and Oxidative Stress and Interferes With Accumulation of Stress-Induced Protein Aggregates - Kaku, Hiroaki; Rothstein, Thomas L. (Frontiers in Molecular Biosciences, 2020)
A key element of cellular homeostasis lies in the way in which misfolded and dysfunctional proteins are handled. Cellular pathways that include proteasomal destruction and autophagic disposal are components of normal proteostasis. Here we report a novel molecule that plays a non-redundant role in maintaining homeostasis, Fas Apoptosis Inhibitory Molecule (FAIM). FAIM is highly conserved throughout evolution and bears no homology to any other protein. We found that FAIM counteracts heat and oxidative stress-induced loss of cell viability. FAIM is recruited to ubiquitinated proteins induced by cellular stress and the levels of stress-induced protein aggregates are much greater in FAIM-deficient cell lines. Primary fibroblasts from FAIM-deficient mice showed the same proteostasis deficits as cell lines. Administration of a mediator of oxidative stress to FAIM-deficient animals induced more ubiquitinated protein aggregates and more organ damage as compared to wild type mice. These results identify a completely new actor that protects cells against stress-induced loss of viability by preventing protein aggregation.